Beekeeping traditions of bee stoking in the ethno-cultural heritage of Right-Bank Polissia of Ukraine: based on field materials - Dmytrenko , Alla (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
The purpose of the study. Based on expeditionary materials, to analyze the traditions of bee stoking that have been formed in beekeeping and apiary beekeeping of the Right-Bank Polissya of Ukraine.Research methodology. The research was based on the principles of historicity, objectivity, systematicity, and complexity; historical research methods (analysis and synthesis, typological, comparative and historical). The ethnological method of research used is the collection of field materials according to the author's questionnaire program; information was collected using the bush method of ethnological research. The field materials collected by the author in different regions of Ukrainian Polissya during 2005-2013 and 2023 are used.Scientific novelty. For the first time in ethnological science, the traditions of bee-killing, their local peculiarities and changes during the second half of the XX and early XXI centuries are studied. The author proves the groundlessness of the thesis about the existence of the so-called swarming system in beekeeping. The used field ethnographic materials are introduced into scientific circulation for the first time.Conclusions. It has been found that two types of devices were used for lighting bees. The oldest were open-fire devices made from improvised materials: tree branches (zubel), linen and wood (golovenka), canvas, flax processing waste, straw, birch bark, and wood mushrooms (kurak). They were set on fire, extinguished, and used to light bees in side and log hives, directing the smoke into the longitudinal opening of the hives. The second type of device is a chimney with a closed fire, in which gunpowder from various trees, including fruit trees, leaves, grass, etc. is burned and the smoke is produced mechanically. The spread of chimneys is associated with the development of frame beekeeping, and in beekeeping and log beekeeping, traditional devices were preserved until the mid-twentieth century, and in some places to this day.